PODER FEMININO E PODER MATERNO: REFLEXÕES SOBRE A CONSTRUÇÃO DA IDENTIDADE FEMININA E DA MATERNIDADE - Thassia Souza Emidio; Francisco Hashimoto (Universidade do Oeste Paulista, 2008)
The feminine and the maternity are themes quite contemplated at the present time. The positioning of the women front to the world, the construction of her identity and the value given to the maternity do part of the reflections and discussions of the modernity. The present article has for purpose to work, through the reflection, the subject of the feminine power and of the maternal power, so that we can demonstrate the power conquered by the women and for the mothers in the construction of her identity in the society. Try to reflect on the factors that structure the relationship of women with motherhood and later with his son, and understand the ways of power established in these relationships. The starting point was thus Psychoanalysis as a source for the theoretical foundation of our thinking and the construction of knowledge. It is hoped that the discussions on this topic may help to look at the feminine and motherhood, to listen and clinical development of the psychoanalysis.